Impact of a pharmacy‐cardiology collaborative management program during initiation of antiarrhythmic drugs. Issue 1 (17th June 2019) - Kibert, Jeffery L.; Franck, Jessica Bovio; Dietrich, Nicole Maltese; Quffa, Lieth H.; Franck, Andrew J.
Abstract: Objective: Antiarrhythmic drugs (AADs) are commonly used for management of atrial fibrillation and other cardiac arrhythmias. However, the use of AADs in clinical practice is challenging due to the risk of serious adverse drug events associated with these medications. Adherence to recommended monitoring parameters may improve safety in these agents. The primary objective of this study was to determine the effectiveness of a pharmacy‐cardiology collaborative approach to AAD management. Methods: This retrospective cohort study was conducted to assess AAD management with a pharmacy‐cardiology collaborative program compared with usual care in a United States Department of Veterans Affairs (VA) medical center. Results: Ninety patients were included for evaluation; 40 in the preintervention group and 50 in the postintervention group. Complete recommended baseline monitoring parameters were obtained for 29 patients (72.5%) in the preintervention group and 47 patients (94%) in the postintervention group ( P < .01). There were significantly more clinical interventions ( P < .01) in the postintervention group, including AAD dose adjustment or discontinuation, interacting medication dose adjustment or discontinuation, electrolyte supplementation, monitoring ordered, and total interventions. Conclusion: The study results demonstrate a statistically significant improvement in adherence to recommended baseline monitoring parameters with a greater number of clinical interventions when a pharmacy‐cardiology collaborative AAD management program was involved compared with usual care. The increased interventions and improved adherence to monitoring parameters may allow for safer use of these agents.